A construção do ethos de sujeitos femininos em canções interpretadas por Elis Regina - Oliveira, Débora Helen de (2022)
So as to provoke a reflection on the role of women in society, we turn our eyes to discourses which function meanings on the (re)existence of the genre that is considered as a point to be investigated. Since colonial times, the role of the female gender has been constituted in several points, as in an erotic, inhumane way, or reduced to representations of objects of a certain control and submission, by which men take their control. The system of patriarchy is not away from this symbolic condition, which provoked (and it still provokes) forms of oppression that reflects on bodies, on minds, on listening, on the discourses of these subjects who have become naturalized throughout history, and thus, some attempts of destruction concerning female subjectivities dragged on through an entire historical system. The research aims at understanding and pointing out how female subjects mean themselves in our corpus of analysis, and we focus on relating this corpus to what Maingueneau (2000) names as constituent discourses which would determine certain meanings on what it is to be a woman; and how these meanings are being reflected in the field of Brazilian Popular Music. Our corpus is composed of four songs so that we can outline interpretation gestures in the lyrics, and certain vocal effects which say about the ethos construction of female subjects in songs related to the field of Brazilian Popular Music, by one of its most famous voices, Elis Regina. This research is theoretically based on French Discourse Analysis, under the name of Dominique Maingueneau, as well as the theory of Nelson Costa, when it comes to indicating the field of Brazilian Popular Music as a possible constituent discourse: the Brazilian literary-musical discourse, in which songs by the interpreter Elis Regina are placed, the point at which the inscription of a linguistic functioning as a mobilizer of symbolic production of the meanings that are determined.